Global Green Building Adoption: An In-Depth Analysis of Trends Worldwide - Susanto, Sony; Ciptadi, Gatot; Hanani, Nuhfil; Anwar, M. Ruslin (Postgraduate School of Universitas Brawijaya, 2024)
Green building has become an increasingly vital topic in global environmental discussions and the construction industry. Sustainable buildings aim to reduce environmental impact, enhance energy efficiency, and create healthier, more comfortable environments. The research aims to understand global trends and practices related to green building concepts and sustainability initiatives. The research methodology employs a bibliometric approach involving the search, selection, and analysis of green building literature. Data bibliographies are analyzed using keyword frequency analysis, citation analysis, and data visualization. The results provide insights into global adoption trends and the roles of specific factors in green building. Various factors influence green building technology adoption, including perceptions of benefits, ease of use, social support, and government policies. This study emphasizes the significance of social, economic, and environmental factors in the diffusion of green building technology. The integration of the Internet of Things (IoT) can enhance efficiency. However, it's important to note that these factors may vary across regions. Further research is necessary for a more comprehensive understanding. In conclusion, this research demonstrates that the adoption of green building technology is influenced by factors such as knowledge, social trust, environmental attitudes, costs, and perceptions of benefits and ease of use. Government support and social factors also play crucial roles in adoption. The integration of the Internet of Things (IoT) holds the potential to improve efficiency. This study is relevant in both advanced and developing countries, such as Indonesia and Africa, promoting the concept of green building for global sustainability Keywords: green building, adoption, TAM